Analisis Ketimpangan Wilayah Terhadap Wacana Pemekaran Wilayah Provinsi di Provinsi Jawa Timur - Nazila Ramadhani; Prayudi Prabowo (Jurnal Ekonomika : INDEPENDEN, 2025)
Regional expansion can be one option that has the potential to reduce inequality in a region. This study was conducted with the aim of analyzing changes in inequality in the province of East Java if it did not undergo and underwent regional expansion based on the discourse of regional expansion. The study used the period from 2010 to 2023. This study uses a quantitative approach. The data used in this study are secondary data sourced from the Central Statistics Agency of East Java Province (BPS). This data was processed using Theil Index analysis. The results of the study indicate that the inequality occurring in all districts/cities undergoes changes if regional expansion occurs, particularly in the expanded regions compared to those that did not undergo regional expansion. The conclusion of this study is that regional expansion can be a solution to reduce and address inequality between regions. Therefore, policies that can enhance economic growth in a region should be implemented to reduce inequality between regions.